Kajian Literatur: Faktor Sosial Budaya yang Mempengaruhi Kejadian Stunting pada Balita di Indonesia - An-Khofiyya, Nida; Fauzia, Kheista Rain; Utamie, Maylinda Putri; Rahayu, Ratna Diah Sri; Fitri, Rihadatus Syahwana; Anggraeni, Yuanita Dwi; Sulistyorini, Anita; Nikmah, Hidayatun (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Stunting is a chronic nutritional issue in children caused by prolonged inadequate nutrient intake due to inappropriate feeding that does not meet nutritional needs. According to data from the 2018 Basic Health Research, the national prevalence of stunting stands at 30.8%, with 11.5% categorized as severely stunted and 19.3% as stunted. Socio-cultural aspects influence health conditions, particularly nutritional fulfillment. The purpose of this study is to review previous studies related to the socio-cultural factors affecting the incidence of stunting in children in Indonesia. The method used in this research is qualitative, with several literature pieces targeting mothers and infants as research subjects in various regions in Indonesia. This study was conducted by searching through Google Scholar and PubMed with the keywords "social," "culture," "stunting," and "children," resulting in 10 journals as samples in this research. The findings of this study are then categorized into two main factors influencing the incidence of stunting social and cultural factors. Social factors include economic level, parental education, and incomplete vaccinations. Cultural factors include habits, taboos, dietary recommendations for mothers and children, and specific cultural practices passed down through generations in each family.